PERTANGGUNGJAWABAN DIREKSI ATAS TINDAKAN KOMISARIS MELAMPAUI KEWENANGAN - Erikson Sihotang (Jurnal Ilmiah Raad Kertha, 2021)
A limited liability company is a legal subject just as humans have rights and obligations. The organs of the limited liability company consist of the General Meeting of Shareholders which is the highest organ of the company, the Commissioner who is in charge of supervising the running of the company, and the Board of Directors is the organ of the Foundation that carries out all company activities and is authorized to represent the company both inside and outside. Each of these organs has limited authority. However, in practice, the commissioners as supervisors of the company often take actions outside their authority, causing the company to lose money, while the directors are responsible for the existence of the company. In such a situation, as long as the board of directors does not authorize the company's commissioners to represent the company, then the commissioner's actions have exceeded his authority (ultravires) so that the responsibility for the company's losses is not borne by the directors but the commissioner must personally be responsible for his actions that harm the company.